The Effect of Online Consumer Review, Social Media Advertisement, and Influencer Endorsement on Purchase Intention - Komara, Edi; Erwand, Debby Noviyanti (Research of Economics and Business, 2023)
This study aims to influence Online Consumer Reviews, Social Media Advertisements, and Influencer Endorsements on Purchase Intentions of Avoskin Skincare Products. This study used a descriptive research design approach with empirical data collected through an online survey of a sample of respondents in Jabodetabek. Empirical data are then processed using the Structural Equation Modeling approach to test some hypotheses proposed. This research is an expansion model, namely by developing existing research by replacing products from previous journals and adding brand loyalty variables. The results of this study, Online Consumer Review, do not affect purchasing intentions on Avoskin skincare products. Meanwhile, Social Media Advertisement and Influencer Endorsement positively affect the intention to buy Avoskin Skincare products. Subsequent studies can be tested using samples and other variables